EFFECTIVENESS OF PROMOTION (CONVENTIONAL AND SOCIAL MEDIA) AND LEVEL OF EASY SERVICE OF HAJJ AND UMRAH MANAGEMENT BUREAU OR AGENT IN THE PANTURA REGION - Susdarwono, Endro Tri (Institut Agama Islam Negeri Metro, 2023)
Promotional activities increase product/service knowledge and consumer's perceived value, thus further increasing their desire to make purchases.This research aims to examine the effectiveness of promotions (conventional and social media) and the level of service convenience of Hajj and Umrah management bureaus or agents in the Pantura area. The approach used in the research is quantitative descriptive. The data collection technique uses a questionnaire with purposive sampling type. The respondents used in this research came from Tegal City and Tegal Regency. The technique for analyzing data applies hypothesis testing based on changes in the Cochran version and analysis of variance through Friedman's two-way level. This research concluded that based on testing the Cochran version of the change hypothesis (Cochran change test), it was concluded that the five promotional means, both conventional and social media, used by Hajj and Umrah bureaus or agents had significant differences in effectiveness. Meanwhile, based on analysis of variance through Friedman's two-way level, the final conclusion was that respondents had significant differences in preferences for the four bureaus or agents for the level of convenience of Hajj and Umrah services. The suggestion from this research is that further research is needed to ensure that promotional tools have a better level of effectiveness than the five promotional tools from this research. And it is recommended to test the hypothesis with a more comprehensive method related to measuring the level of ease of Hajj and Umrah services.